The Relationship Between Social Support and Burnout Among Nurses at 'Aisyiyah Bojonegoro Hospital, East Java, Indonesia - Sudalhar; Adinda Finki Nurbarokah; Septin Maisharah Karyono; Pramono Apriawan Wijayanto; Shofika Fajria Rahman; Afriza Umami (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Hospitals are expected to create a work environment that is safe, comfortable, and supportive of employees' well-being. This study aims to identify the factors that contribute to burnout among nurses, including those originating from the work environment as well as individual factors. Subjects and Method: This study employed an analytical quantitative design with a cross-sectional approach at 'Aisyiyah Bojonegoro Hospital. A total of 114 nurses were selected using a simple random sampling technique. The dependent variable in this study was the level of burnout, while the independent variables included sociodemographic characteristics (age, gender, highest educational attainment, marital status, length of employment, and employment status) and social support. Data were collected using a structured closed-ended questionnaire, and data analysis was conducted using the Spearman's rho test. Results: The results of the analysis showed that social support had a significant effect on burnout (b= 0.04; 95% CI: 0.01 to 0.13; p < 0.001), and gender was also significantly associated with burnout (p= 0.028). In contrast, other variables, including age, educational level, marital status, length of employment, and employment status, did not show a statistically significant association with burnout. Social support emerged as the primary contributing factor in this study. Higher levels of social support were associated with a greater likelihood of positive outcomes, particularly a reduction in burnout levels. Conclusion: There is a significant relationship between social support and burnout, with a negative correlation direction, indicating that higher levels of social support are associated with lower levels of burnout. Meanwhile, gender also demonstrates a significant difference in burnout outcomes. The researchers recommend that hospitals implement regular stress management programs, as well as communication and interpersonal skills training, to help reduce burnout among nurses and enhance their overall well-being.